Pengembangan Media Papan Magnet Siluet Manusia Sehat untuk Pola Hidup Sehat Anak Prasekolah: Pengembangan Media Papan Magnet Siluet Manusia Sehat untuk Pola Hidup Sehat Anak Prasekolah - Vania Dwi Lestari; Andi Hayyun Abiddin; Finta Isti Kundarti (Poltekkes Kemenkes Malang, 2026)
Nutrient deficiency was one of the nutritional problems that could hinder the growth and development process of children. Around the world, many children aged zero to five experienced malnutrition, including a significant number who had low body weight. Insufficient intake of fruits and vegetables caused the body to lack essential nutrients such as vitamins, minerals, and fiber, which potentially led to various illnesses. This research aimed to produce educational media in the form of a healthy human silhouette magnetic board about healthy lifestyles for preschool children. This study used the Research and Development (R&D) method. The research procedure followed the ADDIE model, which consisted of five stages: analysis, design, development, implementation, and evaluation. The study was implemented at TK PKK Gandekan from March to April 2025. The expert validation results showed a very feasible category, and the participant trial results also indicated a very feasible category. The products developed, such as boards with pictures of children’s human organs and magnets with images of fruits and vegetables, were attractive and could be understood by preschool children. Subsequent researchers could test the media on more diverse samples and explore additional health aspects, while educational institutions could adopt it as an interactive learning tool with teacher training support.